Development of Scrabble Game for Learning Arabic Vocabularies in Al-Kautsar Junior High School of Malang - Wilda Rihlasyita (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
This essay describe about the developing of Scrabble Game as a media of leraning Arabic vocabularies. As we know that learning vocabularies is one of the necessity in language learning, especially in learning Arabic language. The purpose of learning vocabularies not only to memorize the vocabularies, but also to use it, both in speaking or writing skill of the students. Professional teacher should teach their students using many kinds of learning media. One of learning media that often used in learning activity is using game. The using of game, especially in Arabic language learning is effective because it can help students to think concretely and it can make them feel happy along the learning activities. Scrabble is one games in learning language in which played by two to four players by placing tiles (each bearing a single letter) into a game board which is divided into a 15×15 grid of squares. This game is suitable with the purpose of learning vocabularies, because it can exercise the students to make a word (vocabulary), based on the material that they have learned. This game is very popular and famous, especially in English version. Moreover, there is also an International championship of English Scrabble game in the word. But in another countries, in which majority of the society learn Arabic language, include Indonesia, this game haven’t popular yet. So, in this paper, the writer will describe the developing of Arabic Scrabble game and the effectiveness of using this game in learning Arabic vocabularies.